RELATION BEETWEEN WORK MOTIVATION AND NURSE JOB SATISFACTION IN THE INPATIENT ROOM OF LEVEL II 03.05.01 DUSTIRA HOSPITAL, CIMAHI CITY 2019 - Oyoh, Oyoh; Rohayani, Lilis; Pragholapati, Andtia (Universitas Tribhuwana Tunggadewi, 2022)
Job satisfaction as an individual's general attitude towards his work. There are two factors that can affect job satisfaction, one of which is motivation because staff job satisfaction is based on motivational factors. Motivation is articulated by encouraging internationals with the help of yourself. Standard data for PMKP 03.05.01 Second Class Hospital in Cimahi City in 2018, employee satisfaction per semester in January-June 2018 obtained 84% (target of ≥90%). This study aims to determine the employment relationship with job satisfaction in the inpatient ward 03.05.01 Hospital II in Cimahi City in 2019. The research design is an analytical survey using cross-sectional. The number of samples was 49 respondents using purposive sampling techniques with inclusion and exclusion criteria. Data collection was done using the Likert scale questionnaire method. Data analysis was carried out through two stages, namely univariate to see the frequency distribution and bivariate to see the relationship (Chi-Square). The results of the study showed that 26 respondents (53.1%) had high work motivation and as many as 27 respondents (55.1%) or greater than respondents who were satisfied to work. The test results prove that there is a significant relationship between work motivation and job satisfaction (p value = 0.001